Monetary reform and world inflation - Aliber, Robert Z. (Beverly Hills, Calif.: Sage Publications, 1973)
This book examines the changes in the international monetary arrangement among the Atlantic nations and the United States. It also considers the issue of reform in international monetary system and economic welfare and political advantages among the nations.
Includes bibliographical references: p. 82.
usc 16/08/2018
Loans
Keywords: Inflation (Finance); Monetary policy; International finance; United States